Emergency response to stormwater contamination: A framework for containment and treatment - Mikelonis, Anne M.; Hawley, Robert J.; Goodrich, James A. (Journal of environmental management, 2021)
This paper presents a Stormwater Emergency Response Framework (SERF) for use in the containment and treatment of stormwater runoff following a hazardous material release. The framework consists of four high level process steps and a decision tree. These resources are intended to assist stormwater managers in fulfilling their emergency response responsibilities within the United States' National Incident Management System. Robust hydraulic and watershed modeling may take weeks to months to develop for a contaminated site, whereas decisions made in the initial hours can have a significant impact on limiting contamination spread. Many web resources are publicly available to assist responders in visualizing stormwater runoff flow paths. A case study provided in this paper also demonstrates how simple calculations may be utilized to estimate peak flows and storage volumes necessary to respond to precipitation events immediately. These calculations are useful for decision makers’ allocation of containment and treatment resources within the impacted area. This includes where to deploy available resources to minimize contamination risks to downstream communities and where supplemental resources from outside partners are urgently needed. •Process steps and decision tree for response to a hazardous material release.•Overview of web resources available to rapidly visualize runoff flow paths.•Framework application to a notional wide-area contamination case study.